Significant Association Between Insertion/Deletion Polymorphism of the Angiotensin-Converting Enzyme Gene and Ankylosing Spondylitis - Inanir, A.; Yigit, S.; Tural, S.; Ozturk, S.D.; Akkanet, S.; Habiboǧlu, A. (Molecular Vision, 2012)
Purpose: Ankylosing spondylitis (AS) is a chronic inflammatory rheumatic disease that characteristically affects the sacroiliac joints and the spine. Also iritis and uveitis can be serious complications of AS that can damage the eye and impair vision. The exact pathogenesis of AS remains poorly understood but genetic factors play a key role in its development. Human leukocyte antigen B27 (HLA-B27) is the major genetic susceptibility marker in AS. To our knowledge, angiotensin converting enzyme (ACE) gene I/D polymorphisms have not yet been investigated in AS patients in Turkish population.This study was conducted in Turkish patients with AS to determine the frequency of I/D polymorphism genotypes of angiotensin converting enzyme gene. Methods: Genomic DNA obtained from 262 persons (122 patients with ankylosing spondylitis and 140 healthy controls) was used in the study. ACE I/D polymorphism genotypes were determined by using polymerase chain reaction with specific primers. Results: There was statistically significant difference between the groups with respect to genotype distribution (p<0.001). When we examine ACE genotype frequencies according to the clinical characteristics there was a statistically significant association between DD genotype and ocular involvement (p=0.04) also sacroiliac joint involvement (p=0.03). Conclusions: As a result of our study, angiotensin converting enzyme gene I/D polymorphism DD genotype could be a genetic marker in ankylosing spondylitis in a Turkish study population. © 2012 Molecular Vision.